Domestication of red jungle fowl: A case study of the red jungle fowl chicks procurement by the communities in Central Bengkulu, Indonesia - JOHAN SETIANTO; BASYARUDIN ZAIN; SUTRIYONO SUTRIYONO; HARDI PRAKOSO (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Setianto J, Zain B, Sutriyono, Prakoso H. 2017. Domestication of red jungle fowl: A case study of the red jungle fowl chicks procurement by the communities in Central Bengkulu, Indonesia. Biodiversitas 18: 183-189. The existence of the red jungle fowl is increasingly pressured by habitat destruction, illegal hunting, and predators’ consumption which may result in an extinction. Conservation of the red jungle fowl had institutionally not been carried out both by the government and private institutions. However, the communities in Central Bengkulu District had done a domestication of the red jungle fowl. Until now, the conservation of the red jungle fowl in a community was not much studied. This study aimed to identify information about the origin of the red jungle fowl chicks, the origin of purchase of chicks, the equipment used for hunting and the chicks purity. Respondents selection was conducted by using a snowball sampling method. The data were obtained by using a combination of in-depth interviews, questionnaires, and a direct observation. The results showed that 38% respondents obtained the chicks from hunting, 40% from buying, 2% from hunting and buying, 6% from buying and conferral, and 14% from conferral. From respondents who did the chicks buying, 4.2% respondents bought the red jungle fowl from the traditional markets, 91.6% bought from hunters, and 4.2% bought from the chicks. Hunting activities were undertaken by 40% respondents, while 60% did not practice hunting activities. From respondents who did the hunting activities, 10% used a net, 30% used racit equipment and 60% used a combination of net and racit. Chicks obtained by respondents, 46% of the red jungle fowl and 54% of the offspring of the red jungle fowl. The red jungle fowl chicks were obtained from nature by hunting in the forests or plantations and from the surrounding communities, either by purchase or conferral. Keywords: Chicks, domestication, hunting, red jungle fowl